2020
DOI: 10.1371/journal.pone.0227769
|View full text |Cite
|
Sign up to set email alerts
|

Successful isolation of Treponema pallidum strains from patients’ cryopreserved ulcer exudate using the rabbit model

Abstract: Clinical isolates of Treponema pallidum subspecies pallidum (T. pallidum) would facilitate study of prevalent strains. We describe the first successful rabbit propagation of T. pallidum from cryopreserved ulcer specimens. Fresh ulcer exudates were collected and cryopreserved with consent from syphilis-diagnosed patients (N = 8). Each of eight age-matched adult male rabbits were later inoculated with a thawed specimen, with two rabbits receiving 1.3 ml intratesticularly (IT), and six receiving 0.6 ml intravenou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 58 publications
1
15
0
Order By: Relevance
“…In silico variant analysis correlated with real-time PCR detection of the mutations associated with macrolide resistance in clinical isolate CDC-SF003. Further, phylogenetics revealed that this strain belonged to the SS14 lineage, which correlated with its enhanced CDC typing method (ECDCT) strain type, 4d9f, as previously reported (7). While this enrichment method yielded good results with isolates, most clinical specimens collected in this study had lower than 100 polA DNA copies/µl of T. pallidum leading us to consider an alternative method.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In silico variant analysis correlated with real-time PCR detection of the mutations associated with macrolide resistance in clinical isolate CDC-SF003. Further, phylogenetics revealed that this strain belonged to the SS14 lineage, which correlated with its enhanced CDC typing method (ECDCT) strain type, 4d9f, as previously reported (7). While this enrichment method yielded good results with isolates, most clinical specimens collected in this study had lower than 100 polA DNA copies/µl of T. pallidum leading us to consider an alternative method.…”
Section: Discussionsupporting
confidence: 84%
“…Molecular studies have relied primarily on T. pallidum strains propagated in rabbits or DNA amplified directly from clinical specimens, because T. pallidum cannot be grown on routine laboratory media. However, advances have been made with in vitro tissue culture and the propagation of T. pallidum in rabbits from cryopreserved genital lesion specimens, which may make routine culture directly from clinical specimens a possibility in the near future (6)(7). Despite these advances, the methods are still time-consuming and impractical for laboratory diagnosis and molecular epidemiological studies of syphilis.…”
Section: Introductionmentioning
confidence: 99%
“…Rabbits are susceptible not only to rabbit (TPeC) but also to hare (TPeL) and human syphilis. Hence, laboratory rabbits played a fundamental role in propagation and diagnostics of human pathogenic treponemes for decades [e.g., (13,14)]. While recent advance in in vitro cultivation of TPA could lead to decreased need of animals for propagation, rabbit infection model will probably remain vital for a variety of biological experiments with treponemes (15).…”
Section: Introductionmentioning
confidence: 99%
“…Surface-exposed lipoproteins of exclusively extracellular pathogen T. pallidum are essential for initial infection, dissemination to distal tissues, and chronic pathogenesis. Study of syphilis has been dependent on propagation of T. pallidum in rabbit testes and examination of orchitic and skin lesions in the rabbit model of infection (Morgan et al, 2002 ; Pereira et al, 2020 ). Recovery of these spirochetes often damages their fragile outer membrane making it difficult to unambiguously determine the localization of various proteins at the subcellular level of T. pallidum , preventing a consensus among researchers on whether a protein is located on the spirochete surface or periplasmic space.…”
Section: Introductionmentioning
confidence: 99%